Hubungan Pengetahuan Keluarga Tentang Penyakit Stroke Dengan Penanganan Pre-Hospital Dirumah Sakit TK II Robert Wolter Mongisidi Manado - Rahmat H. Djalil; Faradila Mifta Suranata; Nelfa Fitria Takahepis (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Stroke is a clinical sign that develops due to a rapid disruption of brain function both focal and global due to rupture of blood vessels and blockages in blood vessels in the brain with symptoms lasting for 24 hours or more. Stroke can be categorized into several types, but in general stroke is divided into two types, namely hemorrhagic stroke and ischemic stroke The severity of stroke depends on which part has been damaged by disease.This research was conducted on families in hospitals. Rumkit R.W. TK II Mongosidi Manado, a population of respondents with a sample number of 37respondents, conducted the study in July to August. This type of research is research using analytical deskritive methods with sectional crosdesign. Sampling techniques use total sampling. Data collection using questionnaires. Furthermore, the data collected, analyzed using the Chi-sqcuare test with a level of meaning (α) ≤ 0.05. Chi-sqcuarestatistical test results obtained a value of p = (a< 0.001). This means that there is a knowledge relationship with the handling of stroke patients that is significant between the relationship of knowledge with the handling of stroke patients in . Rumkit R.W. TK II Mongosidi Manado Conclusion of this study Knowledge relationship with the treatment of stroke patients in the study. Rumkit R.W. TK II Mongosidi Manado Advises the results of this study for developments in the field of nursing next.